Professional Competencies as a Key Factor in Higher Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern conditions, society’s requirements for higher education have changed, and therefore the formation of student competencies is one of the most pressing problems of education at the present stage. The article discusses the key factors of the competency-based approach in education. It is also noted that the competency-based approach reflects the conscious need of society to train people who are not only knowledgeable, but also able to further apply their own knowledge in their specialty.